Opportunities and challenges to improve carbon and greenhouse gas budgets of the forest industry through better management of pulp and paper by-products - Laberge, Sharlène; Courcot, Blandine; Lagarde, Andréanne; Lebel Desrosiers, Simon; Lafore, Karima; Thiffault, Evelyne; Thiffault, Nelson; Bélanger, Nicolas (Frontiers in Environmental Science, 2024)
Developing land use strategies to optimize carbon sinks and improve carbon footprints involves proposing efficient nature-based solutions that industries and businesses can implement while considering financial and legislative constraints. The pulp and paper industry is associated with significant greenhouse gas (GHG) emissions, primarily due to the substantial carbon dioxide (CO2) footprint of its mills. Also, some forestry operations contribute to the release of carbon to the atmosphere in the form of CO2 and methane (CH4). Conversely, this industry could potentially be a significant ally in the fight against climate change by favoring forestry practices that reduce carbon emissions and increase its sequestration, namely by adding value to industrial by-products (e.g. biosolids) instead of treating them as wastes and landfilling them. Notably, the pulp and paper industry has been seeking alternative uses of its by-products, such as fertilizers to maximize tree growth. In this paper, we identify opportunities and challenges that exist for the pulp and paper industry in regard to recycling industrial by-products to: (1) lower GHG emissions directly at the mill and (2) improve its GHG budget by increasing carbon sequestration in forests and plantations. We illustrate our analyses by describing a case study of a pulp and paper mill in southern Quebec, Canada, that uses its biosolids and other by-products as fertilizers. This case study highlights that this strategy could not only contribute to the reduction of GHGs but could also create added value and improve economic returns of forest operations.